Bioengineered miR-124-3p prodrug selectively alters the proteome of human carcinoma cells to control multiple cellular components and lung metastasis in vivo - Linglong Deng; Hannah Petrek; Mei-Juan Tu; Neelu Batra; Ai-Xi Yu; Ai-Ming Yu (Elsevier, 2021)
With the understanding of microRNA (miRNA or miR) functions in tumor initiation, progression, and metastasis, efforts are underway to develop new miRNA-based therapies. Very recently, we demonstrated effectiveness of a novel humanized bioengineered miR-124-3p prodrug in controlling spontaneous lung metastasis in mouse models. This study was to investigate the molecular and cellular mechanisms by which miR-124-3p controls tumor metastasis. Proteomics study identified a set of proteins selectively and significantly downregulated by bioengineered miR-124-3p in A549 cells, which were assembled into multiple cellular components critical for metastatic potential. Among them, plectin (PLEC) was verified as a new direct target for miR-124-3p that links cytoskeleton components and junctions. In miR-124-3p-treated lung cancer and osteosarcoma cells, protein levels of vimentin, talin 1 (TLN1), integrin beta-1 (ITGB1), IQ motif containing GTPase activating protein 1 (IQGAP1), cadherin 2 or N-cadherin (CDH2), and junctional adhesion molecule A (F11R or JAMA or JAM1) decreased, causing remodeling of cytoskeletons and disruption of cell-cell junctions. Furthermore, miR-124-3p sharply suppressed the formation of focal adhesion plaques, leading to reduced cell adhesion capacity. Additionally, efficacy and safety of biologic miR-124-3p therapy was established in an aggressive experimental metastasis mouse model in vivo. These results connect miR-124-3p−PLEC signaling to other elements in the control of cytoskeleton, cell junctions, and adhesion essential for cancer cell invasion and extravasation towards metastasis, and support the promise of miR-124 therapy.